Socio-ecological Drivers of Environmental Antibiotic Resistance and Public Health Vulnerability in Benin City, Nigeria: A Review - Uyi Frank Amadasun; Aimuanmwosa Frank Eghomwanre (FUDMA Journal of Sciences, 2026)
Antimicrobial resistance (AMR) is a serious global public health problem, especially in urban areas of low- and middle-income countries, where environmental reservoirs can increase the spread of pathogens. The present review focuses on the socio-ecological determinants of environmental antibiotic resistance and its associated public health risks in the city of Benin in Nigeria. Using a socio-ecological model (SEM) and a One Health approach, peer-reviewed literature, academic dissertations and policy reports from 2000 to 2026 were systematically synthesized in the six core thematic domains of the One Health approach from PubMed, Scopus, Web of Science and Google Scholar. Informal distribution of antibiotics, non-prescription dispensing and partial course sales is possible because of the large number of patent medicine vendors (PMVs) operating without adequate regulatory oversight. Such practices and poor municipal waste management result in clear socio-ecological leakage points for pharmaceutical residues and multidrug-resistant organisms that enter drainage networks, soils and surface waters. For Benin City, spatial analytic techniques such as kernel density estimation and hotspot analysis are suggested to highlight any clustering of resistance profiles in high-density urban micro-environments, but this has not been done. The city of Benin needs integrated One Health strategies, integration of vendor stewardship, regulation of municipal waste, and local surveillance systems to mitigate environmental AMR.